ANALISIS PEMAHAMAN DAN PEMBELAJARAN MATAN AL-JURUMIYAH PADA PONDOK PESANTREN - Hadira Gustina; Saepudin; Muh. Akib (IAIN Parepare, 2025)
This study aims to analyze students' understanding of the matan al-jurumiyah text, which is a foundational text in the study of Arabic grammar (nahwu) at MTs. The research employs a qualitative approach and was conducted at Pondok Pesantren Al Ikhlas Addary DDI Takkalasi. Data collection methods included observations, interviews with students and educators, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results indicate that some students can explain, define, and apply their understanding of the matan al-jurumiyah text, while others can only understand it without being able to apply it. The main supporting factor is the high motivation to learn, while the main inhibiting factor is a lack of enthusiasm among students. The study concludes that motivation and support are crucial in the learning process of Arabic grammar. The implications of this research suggest that to improve students' understanding, more effective teaching strategies and greater support from educators are necessary.